Changes in Some Soil Chemical Properties of Ultisol Applied by Mulch from Empty Fruit Bunches in an Oil Palm Plantation - Budianta, Dedik; Wiralaga, Ali Yasmin Adam; Lestari, Wahana (JOURNAL OF TROPICAL SOILS, 2010)
Changes in Some Soil Chemical Properties of Ultisol Applied by Mulch from Empty Fruit Bunches in an Oil Palm Plantation (D Budianta, AYA Wiralaga, and W Lestari):  Objective of this research was to study the effect of empty fruit bunches (EFB) applied as mulching on some soil chemical properties of Ultisol in an Oil Palm Plantation. This field experiment was conducted in PT. Sampoerna Agro Tbk Plantation Mesuji, Ogan Komering Ilir of South Sumatra Province at blocks of 22/A, 23/B, 27/C, 33/, 12/A, 12/B, 24/D, 12/C, 00/C, 24/A, 24/B, 10/B, 02/C, 02/D, 11/C, 11/D, 10/A, 10/C, 11/A, and 24/C. The treatment was EFB dosage which are without EFB (control), 40 Mg ha-1 of  EFB applied only once for a year, 80 Mg ha-1 of EFB applied twice for 2 years, 120 Mg EFB/ha applied three times for 3 years, and 160 Mg ha-1 of EFB applied four times for 4 years. The rate of EFB application was 40 Mg ha-1 per year. Every treatment was replicated 4 times, thus total of experiment was 20 units. Soil samples were taken in two differences of deepness which were 0-20 cm and 20-40 cm, respectively. Soil variables observed were soil pH, organic C, cation exchange capacity (CEC), total N, P availability, exchangeable K and Mg, Al and Fe. The results showed that application of EFB had significantly effect on some soil chemical properties such as soil pH and Mg exchangeable Mg for 0-20 cm and total N for 20-40 cm deepness. Meanwhile application of EFB did not have siginificant effects on total organic C, CEC, P-Bray I, exchangeable K, exchangeabile Al and Fe.  It was also shown that some soil chemical properties were generally higher in top soil layer than sub soil layer, except for CEC, P and  exchangeable Al.